PHYTOCHEMICAL INVESTIGATION AND ANTIMICROBIAL PROPERTIES OF DIOSCOREA BULBIFERA TUBER - P, Dahiya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The inhibitory properties of successive extracts from Dioscorea bulbifera (Dioscoreaceae) tubers have been evaluated for the presence of phytochemical constituents and antimicrobial efficacy against multidrug-resistant (MDR) clinical isolates was evaluated. Methods: The tuber of D. bulbifera was oven dried and extracted successively with n-hexane, chloroform, methanol, ethanol, and water. The antimicrobial potential of successive extracts against MDR isolates was studied by agar well-diffusion method. Qualitative phytochemical analysis was performed. Results: Qualitative phytochemical analysis demonstrated the presence of steroids, flavonoids, cardiac glycosides, saponins, and reducing sugars in almost all the extracts tested. Anthraquinones, phlobatanins, and tannins were not reported in any extracts tested. The in vitro antimicrobial activity of various solvents and water extracts of D. bulbifera was further investigated against ten MDR bacteria and three fungi, respectively. Aqueous and chloroform extracts were found to be more potent being capable of exerting significant inhibitory activities against the majority of the isolates such as Escherichia coli, Acinetobacter sp., Salmonella paratyphi, Klebsiella pneumoniae, and Candida albicans. The highest inhibitory activity was observed for K. pneumoniae with wide inhibition zone diameters (17 ± 0.15 mm), followed by E. coli 1(13 ± 0.11) mm, and Acinetobacter sp. (11 ± 0.12). Conclusion: Based on the present study, the extracts of D. bulbifera tubers have shown excellent activity against MDR microbial cultures tested. Further study is recommended for clinical evaluation, of the efficacy of crude extract in herbal medicine that can serve as a base for the development of novel potent drugs and phytomedicines.